2021
DOI: 10.3389/fped.2021.683992
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors of Fungal Peritonitis in Children on Peritoneal Dialysis

Abstract: Objective: To analyse the clinical manifestations, aetiology, prognosis, and risk factors of fungal peritonitis (FP) in children on peritoneal dialysis (PD).Methods: Among 322 children undergoing PD at Children's Hospital of Fudan University, between January 2001 and December 2019, FP cases were retrospectively analysed and compared with those of bacterial peritonitis (BP) to analyse the risk factors of FP.Results: A total of 124 cases of peritonitis were treated, including 11 FP cases in 11 children (0.0019 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The current studies (6,13) revealed that previous use of antibiotics, previous BP, under immunosuppression, higher burden of comorbidities (such as diabetes, malnutrition), prolonged PD duration and loss of residual kidney function are common risk factors for FP. Due to the overgrowth of gastrointestinal fungi and the decline of peritoneal defenses, FP is more likely to develop secondary to antibiotics exposure (7).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The current studies (6,13) revealed that previous use of antibiotics, previous BP, under immunosuppression, higher burden of comorbidities (such as diabetes, malnutrition), prolonged PD duration and loss of residual kidney function are common risk factors for FP. Due to the overgrowth of gastrointestinal fungi and the decline of peritoneal defenses, FP is more likely to develop secondary to antibiotics exposure (7).…”
Section: Discussionmentioning
confidence: 86%
“…FP is relatively rare compared to BP, accounting for only 1-12% of patients with PDAP (6)(7)(8)(9)(10)(11)(12). It was reported that antibiotic use history, prolonged PD duration, malnutrition or hypoalbuminemia, and diabetes are usually identified as important risk factors for the occurrence of FP (6,13). FP is related to high hospitalization rates, catheter removal, permanent transfer to HD, and death (12,14), and the treatment method is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…This was derived from early catheter removal and introduction of antifungal drugs after evidence of the microorganism. The mortality in the worldwide is high if the catheter is not removed early (50-91%) [ 7 ]. The clinical and laboratory characteristics of the four cases are shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%